Implementasi Fungsi Manajemen dalam Penyelenggaraan Dies Natalis HMM-UNPAM Ke-20 Bertema “Bring Me Home” sebagai Upaya Memperkuat Rasa Memiliki dan Solidaritas Organisasi - Tamala Setiarini; Livia Anggun Nazilah; Nayaka Sheridan Husain; Dwi Apriyanti; Lailatul Hikma Roniawan (CV. ITTC INDONESIA, 2026)
This study analyzes the implementation of management functions—Planning, Organizing, Actuating, and Controlling (POAC)—in organizing the 20th Dies Natalis of HMM-UNPAM themed